Strengthening of mechanical and tribological properties in CrFeCuMnNi high entropy alloy through dispersion of TiO2 reinforcement via powder metallurgy processes - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Rao, K. Raja; Mohan, Man; Lee, Hansung; Song, Eunhyo; Ahn, Byungmin (Ceramics International, 2024)
The present study reports the effect of TiO2 reinforcement on the phase, microstructure, mechanical and tribological properties of CrFeCuMnNi/TiO2 high entropy alloy composites (HEACs) processed by powder metallurgy. The results reveal the formation of single-phase face-centered cubic (FCC) structure after 30 h of milling in the original HEA, while TiO2 peaks in the HEACs indicate uniform distribution. After sintering, multiple phases including FCC, Cr-rich, Cr2O3 were observed. The hardness of HEAs increased from 330 ± 10 to 440 ± 10 HV and compressive yield strength increased from 480 to 760 MPa while scarifying the strain from 43.5 to 21 % with TiO2 content. The addition of TiO2 content slightly reduces the coefficient of friction and specific wear rate decreased by 45.16 % due to increased hardness and formation of stable oxide layer on the worn surface inhibits plastic deformation. The addition of TiO2 reduces the dominance of abrasive and adhesive wear and enhances the strength of HEACs.
Keywords: Alloy composites; High entropy alloys; Mechanical; Mechanical and tribological properties; Microstructure mechanical properties; Phase properties; Powder metallurgy process; Property; Single phasis; TiO 2; High entropy alloy; Mechanical properties; Microstructure; Reinforcement; Wear resistance